Peranan Set Elemen Panggung Teater Realis Pada Interior âBunga Rumah Makanâ dan âOperasiâ Gedung Pertunjukkan Sawunggaling Universitas Negeri Surabaya - Poppy Firtatwentyna, Olivia Setiya Budi Martino Dwi Nugroho (Intra, 2014)
The emergence of theater community andÂ arts institution in Indonesia proved that the development of the art of drama/theater is growing. The community is able to deliver good performances, mature andÂ both visually. This research to determine the set of stage elements that are applied to the staging platform